Dual-porosity approach: heat transfer and heat storage processes in porous media - Aron Kneer; Anastasia August; Eduard Alesi; Andreas Reiter; Gert Rehner; Michael Wirtz; Melanie Esslinger; Arnd Hendrik Koeppe; Stéphan Barbe; Britta Nestler (Mathematical and Computer Modelling of Dynamical Systems)
This study emphasizes the significance of understanding groundwater flow behavior for effective contaminant transport and heat storage. Aquifers, with their irregular shapes and variable permeability, exhibit anisotropic flow resistances that affect mass and heat transfer, posing challenges for modeling. The dual-porosity model is used as a numerical approach to calculate macroscopic heat transfer without explicitly resolving the structure. By solving equations for mobile and immobile phases and coupling relevant equations for heat conservation, this model was applied to transient numerical experiments simulating heat transfer and storage in a desktop model filled with glass beads. Results indicate alignment with experimental and numerical models resolving porous structures on the microstructure scale. This methodology offers a comprehensive digital toolbox for solving large-scale heat storage problems in aquifers, contributing to digital and sustainability transformations with reasonable computational demands.